IMAGING OF APPENDICITIS: A SYSTEMATIC REVIEW - Sugih Laksono, Bella (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Delayed diagnosis and treatment might cause gangrene perforation and diffuse peritonitis. This makes radiological exams easy and sensitive and specific. The radiological examination, which includes ultrasound and picture, can be done quickly. In addition to difficult exams like CT scans and barium enemas, these are done.The aim: This study review imaging for appendicitis.Methods: For this systematic review, publications that were published from 2012 to 2023 were taken into account during the search process. This was achieved through the utilization of numerous online reference sources, such as Pubmed and SagePub. The decision was made to exclude review articles, previously published works, and incomplete works.Result: We found seven studies related to the ability of radiological examination in the diagnosis of appendicitis. The research discusses CT scans and ultrasonography.Conclusion: There are several examinations that can be done, for example US, plain radiology and CT scan. An ultrasound examination is an examination that can be carried out quickly and with sufficient accuracy to determine whether a person can be diagnosed as a patient with appendicitis.